How different are offline and online diplomacy? A comparative analysis of public statements and SNS posts by delegates to the United Nations - Sakamoto, Takuto; Araki, Momoko; Ito, Hiroto; Matsuoka, Tomoyuki (Frontiers in Big Data, 2024)
This article investigates the evolving landscape of diplomacy in the digital age, focusing on diplomats at the United Nations (UN) Headquarters in New York. The central inquiry revolves around how diplomatic actors use digital tools to complement or augment traditional face-to-face diplomacy. To address this, we systematically compare a substantial corpus of X posts (tweets) from UN diplomats with their public statements at the United Nations Security Council (UNSC), employing computational social science techniques. While the essence of diplomacy remains consistent across both domains, diplomats display strategic selectivity online. Online communication emphasizes non-security topics, ceremonial matters, and prominent policy stances in comparison with operational issues common in UNSC deliberations. Additionally, online discourse adopts a less confrontational, more public diplomacy-oriented tone, with variations among countries. This study contributes to the field of digital diplomacy and offers insights into how diplomats navigate the digital realm to complement traditional roles. It sheds light on the evolving landscape of international relations by examining diplomacy's dynamics in the UN context.